Challenge of free economic zones in Central and Eastern Europe : International perspectives - Sauvant, Karl P.; Jovanovic, Miroslav N.; Zaitsev, Nikolai (New York United Nations, 1991)
Contiene: Free economic zones -- Establishment -- Institutional and economic issues -- Domestic and international linkages -- The foreign exchange challenge -- Promotion -- Case studies -- Annex: Nakhodka zone.
Keywords: LIBERALIZACION DEL INTERCAMBIO; ZONAS DE LIBRE COMERCIO